2018
DOI: 10.1097/sla.0000000000003172
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline Reduces Scar Thickness and Improves Collagen Architecture

Abstract: Objective: To investigate the effects of local doxycycline administration on skin scarring. Background: Skin scarring represents a major source of morbidity for surgical patients. Doxycycline, a tetracycline antibiotic with off-target effects on the extracellular matrix, has demonstrated antifibrotic effects in multiple organs. However, doxycycline's potential effects on skin scarring have not been explored in vivo. Methods: Female C57BL/6J mice underwent dorsal wounding following an established splinted excis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…The decreased biomechanical function of scars highlights the need for clinical therapies to improve the scar tensile strength 66 . It is reported that very few effective therapies exist which inhibit scar formation while maintaining scar tensile strength 67 . Ward et al revealed that subcutaneous injection of GsMTx4 improved muscle strength of mice 68 .…”
Section: Discussionmentioning
confidence: 99%
“…The decreased biomechanical function of scars highlights the need for clinical therapies to improve the scar tensile strength 66 . It is reported that very few effective therapies exist which inhibit scar formation while maintaining scar tensile strength 67 . Ward et al revealed that subcutaneous injection of GsMTx4 improved muscle strength of mice 68 .…”
Section: Discussionmentioning
confidence: 99%
“…Doxycycline is a broad-spectrum tetracycline-class antibiotic that inhibits the 30S ribosome subunit; the drug also has an anti-inflammatory effect [ 53 ]. Several reports on the effects of doxycycline on the ocular system [ 93 ], the oral cavity, intracranial venous hypertension [ 94 ], skin scarring [ 49 ], and rosacea have appeared. In patients with intracranial venous hypertension, doxycycline inhibits angiogenesis by reducing microvessel density, suppressing MMP-3 overexpression, and reducing VEGF and TGF-β levels [ 94 ].…”
Section: Rosaceamentioning
confidence: 99%
“…For example, Qi et al reported that hydrogels made from sericin (a silk-derived natural biomaterial) resulted in accelerated healing with reduced inflammation and features of regeneration (e.g., increased hair follicle neogenesis) in a preclinical mouse model (Qi et al, 2018). Identification of novel anti-scarring drugs is also an active area of research; for instance, a study from our laboratory recently established doxycycline as a putative anti-scarring agent which reduces fibrosis and promotes features of regeneration in a splinted mouse wound healing model (Moore et al, 2018). Translation of these discoveries into a clinical setting, and continued exploration of scarring from the lenses described in this article, will lead to continued advancement in our ability to treat and improve craniofacial wound healing.…”
Section: Future Directions: Toward Scarless Craniofacial Healingmentioning
confidence: 99%